2010
DOI: 10.5424/sjar/2010084-1239
|View full text |Cite
|
Sign up to set email alerts
|

Effect of drip irrigation intensity on soybean seed yield and quality in the semi arid Harran plain, Turkey

Abstract: Additional key words: drought stress; irrigation level; seed oil and protein; semi-arid climatic conditions. ResumenEfecto de la intensidad del riego por goteo en el rendimiento y calidad de las semillas de soja en la llanura semiárida de Harran, TurquíaSe cultivó soja (Glycine max L.) en 2003 y 2004, en el clima semiárido de la llanura de Harran, Sanliurfa, Turquía, para determinar el efecto de diferentes niveles de estrés hídrico sobre el crecimiento, algunas variables fisiológicas y la composición de la sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
23
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 24 publications
6
23
2
1
Order By: Relevance
“…In the present research the oil content, regardless of the treatment, varied around 20% and the protein content was greater than 35%. With regard to the percent of oil and protein content, the results reported here are similar to those of Kirnak et al (2010), who emphasized that water stress affects grain quality. The differences between the results of the present study and those reported by others can be attributed to different time, severity and duration of drought, metabolic state of the plant, stage of growth, applied agrotechnical measures or even the genotype or cultivar response to irrigation (Reddy et al, 2004;Bettaieb et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In the present research the oil content, regardless of the treatment, varied around 20% and the protein content was greater than 35%. With regard to the percent of oil and protein content, the results reported here are similar to those of Kirnak et al (2010), who emphasized that water stress affects grain quality. The differences between the results of the present study and those reported by others can be attributed to different time, severity and duration of drought, metabolic state of the plant, stage of growth, applied agrotechnical measures or even the genotype or cultivar response to irrigation (Reddy et al, 2004;Bettaieb et al, 2011).…”
Section: Discussionsupporting
confidence: 88%
“…Similarly to our results, Al-Tawaha et al (2007) found that irrigation had no effect on the oil content, regardless of the amount of irrigation water applied. In contrast to our results, Kirnak et al (2010) examined the effect of different drip irrigation rates on soybean yield and quality over two years under semi-arid conditions in Turkey (Harran Plain) and recorded the highest oil content of non-irrigated (I 0 ) soybean in both years. On the other hand, the same researchers established a much broader interval of oil content variation between the treatments they studied (15.30-17.96% in 2003 and 16.40-20.10% in 2004).…”
Section: Discussioncontrasting
confidence: 87%
“…The results of statistical regression analysis indicated a polynomial relation among the oil content of soybean and the amount of irrigation water used during the growing season (Figure 2). Contrary to this research, Kirnak et al (2010) established an inverse linear relation among the seasonal water demand of soybean.…”
Section: Resultsmentioning
confidence: 84%
“…Contrary to this research, Kirnak et al (2010) established a power function among the amount of water used during the soybean growing season and the protein content of soybean grown under semi-arid conditions in Turkey.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation